Summary report of the 2019 Diversity and Inclusion Task Force of the National Society of Genetic Counselors. Issue 2 (30th March 2020) - Channaoui, Nadine; Khan, Ambreen; Wiesman, Chana; Bui, Kara; Cunningham, Mitch; Brown, Kaitlyn; Wolfe Schneider, Kami; Platt, Kristal; Hodges, Priscila Delgado; Thompson, Nicole; Haas, Bruce; Strang, Katie; et al.
Abstract: The size and reach of the genetic counseling profession have expanded on a global scale since the 1970s. Despite this growth, the profession of genetic counseling has remained demographically homogenous. Promoting a culture of inclusivity that supports visible and invisible diversity and leveraging that culture not only expands perspectives represented in the field, but also helps foster equity in genetic services. This report summarizes the formation, implementation, and outcomes of the 2019 Diversity and Inclusion Task Force (TF) of the National Society of Genetic Counselors (NSGC), including the group's responses to their allotted charges from the NSGC Board of Directors. The recommendations generated by the TF aim to aid in the (1) establishment of infrastructure for ongoing diversity, inclusion, and equity (DEI) work by collaborating with a DEI organizational expert and forming a DEI advisory group within the NSGC, (2) development of specific short‐term DEI initiatives, and (3) identification of seven areas of focus areas that must be addressed in order to create meaningful and measurable DEI improvements. The efficacy of these recommendations will depend on the consistency and creativity of implementation, shared responsibility, sufficient resources allocated to DEI initiatives, and measurable outcomes.